Environmentally Friendly Livestock Waste Management in High-Population Areas in Karang Ploso Malang Regency East Java - Muhammad Arwani; Abdul Hakim; Agus Budiarto; Gatot Ciptadi; Yudit Oktanella (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This abstract explores the need for integrated development in the agricultural and livestock sectors of Ngenep Village, Karangploso, Malang Regency, focusing on utilizing livestock waste effectively. Method: The study details the steps to develop a system for producing organic fertilizer and animal feed from agricultural and livestock waste. It highlights the successful implementation within the